US guided missiles the definitive reference guide - Yenne, Bill (Crécy, 2012)
Illustrated with excellent archival and contemporary photography, this book features every single U.S. guided missile, with special coverage of the famous jet-powered winged missiles of the 1950s cult Cold War.